Investigating the empirical relationship of corporate real estate sustainable management with corporate environmental sustainable objectives / Nurul Sahida Fauzi ... [et al.] - Fauzi, Nurul Sahida; Johari, Noraini; Chuweni, Nor Nazihah; Zainuddin, Ashrof; Sanuddin, Yuhadi (2021)
Businesses are now obligated to measure environmental impact against their financial impact. Besides focusing on the corporate objectives of maximising value and reducing risks, they now need to ensure that their corporate environmental sustainable objectives are achieved. Previous research reveals a lack of discussions on corporate real estate sustainable management (CRESM) especially those matters linked with corporate environmental sustainable objectives. Therefore, this research was conducted to identify the relationship between them to fill the gap. Previous research was reviewed and analysed using content analysis and metric analysis. Thus, six relationships were identified. These findings could facilitate further investigation into the related fields to encourage more corporations to be involved with sustainability.